2008
DOI: 10.1371/journal.pone.0002386
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Ubiquitin-Mediated Pathway in Apicomplexan Parasites: A Potential Strategy to Interfere with Parasite Virulence

Abstract: BackgroundReversible modification of proteins through the attachment of ubiquitin or ubiquitin-like modifiers is an essential post-translational regulatory mechanism in eukaryotes. The conjugation of ubiquitin or ubiquitin-like proteins has been demonstrated to play roles in growth, adaptation and homeostasis in all eukaryotes, with perturbation of ubiquitin-mediated systems associated with the pathogenesis of many human diseases, including cancer and neurodegenerative disorders.Methodology/Principal FindingsH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
136
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(143 citation statements)
references
References 124 publications
5
136
2
Order By: Relevance
“…The 60 S ribosomal protein L27a (PFF0885w) was found to be ubiquitylated at ring stage exclusively (5 spectral counts), and seven ubiquitin conjugates were trophozoite-specific (Table 3). Two of them are members of the ubiquitin/proteasome system in P. falciparum (10). UFD2 (PFD0265w) is a U-box ubiquitin ligase involved in the endoplasmic reticulum-associated protein degradation pathway Ubiquitylation in P. falciparum NOVEMBER 18, 2011 • VOLUME 286 • NUMBER 46…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 60 S ribosomal protein L27a (PFF0885w) was found to be ubiquitylated at ring stage exclusively (5 spectral counts), and seven ubiquitin conjugates were trophozoite-specific (Table 3). Two of them are members of the ubiquitin/proteasome system in P. falciparum (10). UFD2 (PFD0265w) is a U-box ubiquitin ligase involved in the endoplasmic reticulum-associated protein degradation pathway Ubiquitylation in P. falciparum NOVEMBER 18, 2011 • VOLUME 286 • NUMBER 46…”
Section: Resultsmentioning
confidence: 99%
“…In P. falciparum, previous in silico studies identified four predicted sources of ubiquitin moieties. The polyubiquitin gene PFL0585w contains five conserved ubiquitin repeats (9,10). The two ubiquitin fusion proteins PfUB S27a and PfUB L40 (PF14_0027 and PF13_0346, respectively) contain a ubiquitin moiety at their N-terminal side (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HECT (homologous to the E6-AP carboxyl terminus) ubiquitin ligase E3] (Dataset S1), another gene in the ubiquitin-mediated pathway (34). Given the role of this pathway in directing protein degradation and recycling, it is possible that alterations in these genes create changes in stress responses or protein turnover of key resistance modulators that allow the parasite to survive under drug pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, histone H4 sumoylation is associated with decreased gene expression (136). The malaria parasite genomes contain a number of protein homologues of E1, E2, and E3 and a number of proteases that might be involved in removing the Ubl modifications (118,120). In an effort to identify the proteome of PfSUMO modified proteins, Issar et al (74) identified sumoylated histone H4 from P. falciparum.…”
Section: Chromatin Modifications: Deposition Recognition and Functionsmentioning
confidence: 99%